Tectonic and lithological controls on fluvial landscape development in central-eastern Portugal: Insights from long profile tributary stream analyses - Martins, António (2017)
This study examines the long profiles of tributaries of the Tagus and Zêzere rivers in Portugal (West Iberia) in order to provide new insights into patterns, timing, and controls on drainage development during the Quaternary incision stage. The studied streams are incised into a relict culminant fluvial surface, abandoned at the beginning of the incision stage. The streams flow through a landscape with bedrock variations in lithology (mainly granites and metasediments) and faulted blocks with distinct uplift rates. The long profiles of the analyzed streams record an older transitory knickpoint/knickzone separating (1) an upstream relict graded profile, with lower steepness and higher concavity, that reflects a long period of quasi-equilibrium conditions reached after the beginning of the incision stage, and (2) a downstream rejuvenated long profile, with steeper gradient and lower concavity, particularly for the final reach, which is often convex. The rejuvenated reaches testify to the upstream propagation of several incision waves, interpreted as the response of each stream to increasing crustal uplift and prolonged periods of base-level lowering by the trunk drainages, coeval with low sea level conditions. The morphological configurations of the long profiles enabled spatial and relative temporal patterns of incisions to be quantified. The incision values of streams flowing on the Portuguese Central Range (PCR; ca. 380–150 m) are variable but generally higher than the incision values of streams flowing on the adjacent South Portugal Planation Surface (SPPS; ca. 220–110 m), corroborating differential uplift of the PCR relative to the SPPS. Owing to the fact that the relict graded profiles can be correlated with the Tagus River T1 terrace (1.1–0.9 My) present in the study area, incision rates can be estimated (1) for the streams located in the PCR, 0.38–0.15 m/ky and (2) for the streams flowing on the SPPS, 0.22–0.12 m/ky. The differential uplift inferred in the study area supports the neotectonic activity of the bordering faults, as proposed in previous studies based upon other geological evidence.